A Cross-Sectional Study on Incidence and Predictors of Self-Reported Dental Anxiety among Nigerian Public Primary Schoolchildren - Eseadi, Chiedu; Surjaningrum, Endang R. (European Journal of General Dentistry, 2024)
Objective The presence of dental anxiety in Nigerian public primary schools may be one of the main obstacles preventing schoolchildren from effectively utilizing dental care services. The main objective of this cross-sectional study was to investigate the incidence and factors associated with self-reported dental anxiety among Nigerian public primary school children.Materials and Methods A cross-sectional, observational design was employed to examine 434 primary schoolchildren (aged 6–9 years) from selected schools in Abia State, Southeastern Nigeria. Data collection was conducted using the Modified Dental Anxiety Scale, which includes 5-point Likert responses, five questions, and demonstrates good internal consistency.Results The findings indicate that there was no statistically significant difference in the occurrence of dental anxiety between male and female schoolchildren (p = 0.374). In total, 1.9, 8.7, 10.1, 36.4, and 42.9% of the schoolchildren reported experiencing no dental anxiety, mild, moderate, extreme, and severe levels of dental anxiety, respectively. Furthermore, the results reveal that 2.1% of the variance in children's dental anxiety scores could be accounted for by factors such as gender, age, socioeconomic status, and parental education. However, the influence of gender (B = 0.183; p = 0.060; 95% confidence interval [CI]: –0.008 to 0.374), age (B = –0.128; p = 0.187; 95% CI: –0.318 to 0.062), socioeconomic status (B = –0.067; p = 0.124; 95% CI: –0.152 to 0.018), and parental education (B = –0.045; p = 0.420; 95% CI: –0.154 to 0.064) on schoolchildren's dental anxiety was not significant.Male and female schoolchildren did not have significantly different dental anxiety levels. Gender, age, socioeconomic status, or parent education level did not significantly predict the dental anxiety among schoolchildren.Conclusion School-based interventions need to be targeted to reduce dental anxiety among male and female primary schoolchildren in the study area. Clinicians should consider providing interventions to manage dental anxiety in children with moderate to severe levels of anxiety.
Keywords: children; dental anxiety; dental appointment; dental care; Nigeria